207k views
1 vote
If f(x)=2x^2+3 and g(x)=x-2, what is (f+g)(2)?

User Pajamas
by
4.4k points

2 Answers

4 votes

Answer:

11

Explanation:

(f+g)(2) means f(2)+g(2).

f(2) means we need to replace the x's in f(x)=2x^2+3 with 2.

This gives us f(2)=2(2)^2+3.

Let's simplify f(2)=2(4)+3=8+3=11.

g(2) means we need to replace the x's in g(x)=x-2 with 2.

This gives us g(2)=2-2

Let's simplify g(2)=0.

Now f(2)+g(2) means we just add the result of f(2) to the result of g(2).

So the problem is what is 11+0?

Answer is 11

User Paxz
by
4.6k points
2 votes


(f+g)(x)=2x^2+3+x-2=2x^2+x+1\\\\(f+g)(2)=2\cdot2^2+2+1=8+3=11

User JohnDotOwl
by
4.6k points